KONTRIBUSI KELINCAHAN DENGAN KEMAMPUAN DRIBBLING BOLA PADA SEPAKBOLA DI SMAN 1 KECAMATAN INUMAN - Agust., S.Pd, M.Pd, Kristi; ', Supriadi; ', Drs. Saripin., M.Kes AIFO (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the lack of soccer dribbling skills in SMAN 1 District of Inuman. It is suspected factor agility. Therefore, the purpose of this study was to determine whether there is a contribution the agility with soccer dribbling ability at SMAN 1 District of Inuman. This type of research is correlational comparing the measurement results of two different variables in order to determine the level of contribution between these variables. As the independent variable (X) is agility while the dependent variable (Y) is a soccer dribbling ability . The sample in this study is malae student class XI who numbered 30 people (purposive sampling). Data obtained from the results of the test agility and ability tests dribbling. Based on the research that has been done on male students of class XI SMAN 1 District of Inuman obtained rhitung = 0422> rtabel = 0.361, meaning there is a significant corelation between agility with soccer dribbling ability. Next look for the big contribution of variable X to Y, count r 2 x 100% = 17.8%. It can be concluded